Real-time assessment of kidney allografts during HOPE using flavin mononucleotide (FMN) — a preclinical study - Sousa Da Silva, Richard X.; Darius, Tom; Mancina, Leandro; Eden, Janina; Wernlé, Kendra; Ghoneima, Ahmed S.; Barlow, Adam D.; Clavien, Pierre-Alain; Dutkowski, Philipp; Kron, Philipp (Frontiers in Transplantation, 2023)
The gap between available donor grafts and patients on the waiting lists is constantly growing, leading to an increased utilization of high-risk kidney grafts. The use of these organs requires new strategies of organ optimization and assessment before transplantation. Hypothermic machine perfusion (HMP) is standard for kidneys obtained from donation after circulatory death (DCD), whereas evidence for additional oxygenation to HMP is still very limited and an objective assessment of HMP-perfused kidneys is lacking. Recently, mitochondrial flavin mononucleotide (FMN) release during machine liver perfusion was shown to be predictive for post-transplant graft function. This study aims to determine whether FMN is also suitable for the assessment of kidney injury. In a porcine model, the feasibility of assessing DCD kidney grafts during hypothermic oxygen perfusion (HOPE) was explored. A DCD group with warm ischemia times (WIT) of 30 and 60 minutes, mimicking a clinically relevant scenario, and a DBD group (donation after brain death) as control. Kidneys were subjected to two hours of static cold storage (SCS) followed by two hours of end-ischemic HOPE with real-time FMN measurement. FMN values were related to damage-associated molecular patterns (DAMPs) and ATP production. Two DCD kidneys with 30-minute WIT additionally underwent normothermic perfusion for two hours to compare DAMPs release with hypothermic perfused kidneys. We demonstrate, first, feasibility of FMN measurement in perfused kidneys, and secondly its correlation with the WIT. Accordingly, perfusate FMN was significantly higher in the 60-minute WIT group (n=4) compared with the 30-minute WIT (n=4) and DBD group (n=4). FMN release also correlated with DAMP signaling, such as 8-OHdG and HMGB1 release. Finally, ATP replenishment was best in DBD kidneys, followed by DCD kidneys with 30 minutes WIT and then by 60 minutes of WIT. This study proves feasibility of FMN measurement in kidneys during HOPE. In addition, we reveal a correlation between FMN quantification and pre-existing kidney injury. Based on this, real-time FMN measurement during HOPE may be an objective assessment tool to accept high-risk kidneys for transplantation while minimizing post-transplant dysfunction, moving away from former “gut feeling” towards objective criteria in accepting marginal kidney grafts for transplantation.